Structure and phase transition peculiarities in solid nitrous oxide and attempts at their explaination - Drobyshev, A.; Aldiyarov, A.; Korshikov, E.; Kurnosov, V.; Sokolov, D.; Tokmoldin, N. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
Cryogenic vacuum deposited films of nitrous oxide were studied at the following conditions: a mirror-like silver-coated copper substrate; deposition temperature 16 K; gas phase pressure during deposition 10–3 Pa. Anal-ysis of the IR-spectrometric and thermodesorption data leads to the following conclusion. The transition from the amorphous to crystalline state in the vicinity of 40 K proceeds in several steps which reflect relaxation processes related to different molecular vibrations. The differences in the temperature intervals of the transitions are determined by the activation energies of relevant vibrations. It was shown that cryocondensation at 16 K is accompanied by appearance of flashes on the condensate surface. Based on the uniform nature of the observed processes, a model based on several possible isomorphic molecular states of nitrous oxide is suggested.